Grundtvig-samlingen på Instituttet for dansk kirkehistorie - Bugge, Knud Eyvin (Grundtvig-studier, 1958)
The Grundtvig Collection at the Institute of Danish Church History.By K. E. Bugge.In the autumn of 1956 a new Institute for Danish Church History was inaugurated under the auspices of the University of Copenhagen. Shortly afterwards there appeared several articles by the Head of the Institute, Prof. Hal Koch, in which, among other things, he called attention to the exceptionally fine Grundtvig collection belonging to the Institute. The purpose of the present article is to give a brief account of some of the rarities contained in the collection.The main part of it consists of the so-called “ Thorsen-Collection”, which was made by the late Inspector N. F. Thorsen, who died in 1946, and which was bought in 1947 by the University of Copenhagen with a view to its use by the proposed Institute for Danish Church History. The catalogue of the Thorsen Collection contains about 850 items, even if periodicals and works in several volumes are reckoned as single items. The size of the collection is partly due to the fact that Thorsen acquired not only one, but several copies of a single work of Grundtvig’s, if these were printed on different kinds of paper. Furthermore, he also endeavoured to get hold of uncut copies, copies with their original dust-jackets, and works containing dedications in Grundtvig’s own handwriting to members of his family or of his circle of friends. Finally, the collection also contains some copies of proof together with a small collection of books which belonged to Grundtvig.Besides books and articles the Thorsen collection also contains a series of cuttings from contemporary daily papers and periodicals. In addition, there is a fairly large collection of works dealing with Grundtvigianism and Grundtvig’s family. In 1950 the collection was supplemented by the purchase of a picture collection containing 83 pictures and with a collection of about 170 cuttings from newspapers and periodicals. Since then the collection has been further supplemented, partly by gifts and partly by purchases. The present article gives a survey of the way in which the Institute’s Grundtvig collection provides us with new information about Grundtvig’s life and literary work, and shows how on the basis of this material we can correct various things which had formerly been reckoned as facts.The most interesting feature of the part of the collection which is catalogued under the title, “ Grundtvig’s ancestors and family” , is the books by and about F. L. Grundtvig. The Institute possesses a complete set of copies of the weekly “ Brevduen” (“ The Messenger Dove” ) which F. L. Grundtvig issued as a boy together with Svend Høgsbro and the brothers Joakim and Niels Skovgaard. In addition, there are a good many books bearing the signature of F. L. Grundtvig; again, others have belonged to members of the inner family circle and are therefore adorned with dedicatory poems in F. L. Grundtvig’s own handwriting. Unfortunately none of these poems was known in 1955, when Høirup’s book on F. L. Grundtvig appeared.In the part of the collection which is catalogued under the title, “ Grundtvig’s collection of books” , there are two books in particular which arouse our interest. The first is Grundtvig’s own copy of the book, “ Cathecismi Forklaring” (“ Explanation of the Catechism” ), 1779, by his father, Johan Grundtvig, which was presented to Grundtvig in January 1791. Here and there in the book various additions have been inserted in Grundtvig’s handwriting. Next may be named Ulfila’s Gothic translation of the Bible in the edition of 1805 by J. Christian Zahn. The book belonged to Grundtvig, and later to his son, Svend Grundtvig. Grundtvig provided the glossary in the latter part of the book with numerous notes, both in ink and in pencil. These notes give us an interesting insight into Grundtvig’s ideas about the etymology of different words. A real tit-bit for philologists!Finally we must mention two smaller sections of the Institute’s Grundtvig collection: first a collection of notes on Grundtvig’s hymns and poems, and then a collection of unpublished material concerning Grundtvig. The lastnamed collection contains, among other things, an unpublished letter, dated 28/4 1867, dealing “ inter alia” , with Grundtvig’s mental illness in 1867.The Institute’s Grundtvig collection is probably one of the three most complete Grundtvig collections which exist. Only the collections in the Royal Library and in the Grundtvig Library at Vartov can be compared with the one described here. These three great collections supplement each other admirably, since each of them contains Grundtvigiana which the two others do not possess.